Effects of single-anastomosis duodenal–ileal bypass with sleeve gastrectomy on gut microbiota and glucose metabolism in rats with type 2 diabetes - Wang, Lun; Li, Shixing; Jiang, Tao (Frontiers in Microbiology, 2024)
Background Bariatric and metabolic surgery often leads to significant changes in gut microbiota composition, indicating that changes in gut microbiota after bariatric and metabolic surgery might play a role in ameliorating type 2 diabetes (T2D). However, the effects of single-anastomosis duodenal-ileal bypass with sleeve gastrectomy (SADI-S) on gut microbiota in T2D remain unclear.Objectives To investigate the effects of SADI-S on gut microbiota and glucose metabolism in T2D rats.Methods Nineteen T2D rats were randomly divided into the SADI-S group (n = 10) and the sham operation with pair-feeding group (sham-PF, n = 9). Fecal samples were collected to analyze the gut microbiota composition with 16S ribosomal DNA gene sequencing.The fasting blood glucose and glycated hemoglobin were measured to evaluate the effects of SADI-S on glucose metabolism. The ACE and Chao index values were significantly lower in the SADI-S group than in the sham-PF group, indicating that indicating that species richness was significantly lower in the SADI-S group than in the sham-PF group (p < 0.05). Compared with the sham-PF group, the SADI-S group showed significantly lower Shannon index and higher Simpson index values, indicating that the species diversity was significantly lower in the SADI-S group than in the sham-PF group (p < 0.05). At the genus level, SADI-S significantly changed the abundances of 33 bacteria,including the increased anti-inflammatory bacteria (Akkermansia and Bifidobacterium) and decreased pro-inflammatory bacteria (Bacteroides). SADI-S 3 significantly decreased the fasting blood glucose and glycated hemoglobin levels. The blood glucose level of rats was positively correlated with the relative abundances of 12 bacteria, including Bacteroides, and negatively correlated with the relative abundances of seven bacteria, including Bifidobacterium.Conclusions SADI-S significantly altered the gut microbiota composition of T2D rats, including the increased anti-inflammatory bacteria (Akkermansia and Bifidobacterium) and decreased pro-inflammatory bacteria (Bacteroides).The blood glucose level of rats was positively correlated with the abundances of 12 bacteria, including Bacteroides, but negatively correlated with the relative abundance of seven bacteria, including Bifidobacterium. These alternations in gut microbiota may be the mechanism through which SADI-S improved T2D. More studies should be performed in the future to validate these effects.